Myeloid-derived suppressor-like cells – does their frequency change in patients with different stages of CRC? - Brčerević, Irina; Doder, Radoje; Perišić, Nenad; Petrović, Stanko; Vojvodić, Danilo (Vojnosanitetski pregled, 2023)
Background/Aim. Colorectal cancer (CRC) is one of the most common cancers in the population, often leading to lethal outcomes. Myeloid-derived suppressor cells (MDSCs) belong to a heterogeneous group of immature cells thought to have an immunosuppressive effect that may aid in tumor development and spreading. The aim of this study was to analyze the frequency and significance of MDSC-like cells at different stages in patients with CRC. Methods. Peripheral blood (PB) samples of 83 patients at different stages of the disease and 12 healthy subjects (control group) were analyzed. MDSC-like cells were identified and enumerated in the PB samples of the participants based on the immunophenotypic characteristics of the cells. Results. A statistically significant increase in the absolute and relative number of polymorphonuclear (PMN) MDSC (PMN-MDSC)-like cells was observed in the PB of all the patients with CRC, compared to the healthy control group (p < 0.0001). No significant increase was observed in monocytic MDSC (M-MDSC)-like cells when they were analyzed without CRC stage stratification (p > 0.05). When the relative and absolute numbers of PMN-MDSC-like cells were analyzed in relation to the stages of CRC disease (TNM classification), a statistically significant difference was observed between the control group and patients in stages III and IV of the disease (p = 0.0005 vs. p = 0.0003 and p < 0.0001 vs. p < 0.0001, respectively). There was, as well, a significant difference when the numbers of PMN-MDSC-like cells in patients in stages I and II were compared to numbers in patients in stage IV of the CRC (p = 0.0161 vs. p < 0.0001 and p = 0.0065 vs. p < 0.0001, respectively). A statistically significant difference in the relative and absolute number of M-MDSC-like cells was observed only between patients in stages II and IV of the disease (p = 0.0014 and p = 0.0002, respectively). The highest number of MDSC-like cells was observed in stage IV of the disease according to the TNM classification. A positive correlation between the presence of these cells and the number of organs affected by metastatic changes was observed (p < 0.0001 for the relative and absolute number of PMN-MDSC-like cells and p = 0.003 and p = 0.0004 for the relative and absolute number of M-MDSC-like cells). Conclusion. CRC patients had a statistically significant increase in PMN-MDSC-like cells compared to healthy controls. The increase in absolute and relative numbers of these cells mostly follows the growth and progression of CRC, while a statistically significant difference in the number of M-MDSC-like cells is observed only between stages II and IV of the disease. The absolute and relative numbers of both subtypes of MDSC-like cells significantly correlate with the number of organs affected by CRC metastases.